Forecasting the magnitude of the largest expected earthquake - Robert Shcherbakov; Jiancang Zhuang; Gert Zöller; Yosihiko Ogata (Nature Communications, 2019)
Forecasting aftershock earthquakes is a critical step in improving seismic hazard mitigation. The authors here combine Bayesian methods with extreme value theory to tackle this problem - and manage to estimate the maximum magnitude of an expected earthquake as well as the arrival times in a pre-defined window.